Analytical fatigue life prediction of shot peened Inconel 718. (August 2018) - Klotz, T.; Miao, H.Y.; Bianchetti, C.; Lévesque, M.; Brochu, M.
Highlights: Crack initiation location can be predicted on shot peened Inconel 718. Navarro and de los Rios propagation and Chan crack initiation models were coupled. Residual stress and cold work profiles redistribution were accounted for. The model predicts the crack initiation location and the fatigue life. Abstract: High and low cycle fatigue tests performed on shot peened Inconel 718 can result in different crack initiation locations and mechanisms as well as in a wide range of fatigue lives depending on shot peening parameters. A model coupling Navarro and de los Rios crack propagation with Chan's crack initiation models is developed and successfully used to predict crack initiation location and fatigue life of shot peened and unpeened Inconel 718 specimens tested in high and low cycle fatigue at room temperature. Redistributed residual stresses and cold work profiles are added to the propagation model and the crack initiation model is modified to account for the residual stresses. Such a model could lead to significant experimental cost reduction by avoiding the trial and error process currently required to define optimal shot peening parameters.